Economic assessment of transport and logistics system‟s contribution to national economic growth - Aliyeva, R.; Aliyev, F.; Алієва, Р. Т.; Алієв, Ф. З. (Харківський національний автомобільно-дорожній університет, 2025)
The article provides a comprehensive analysis of the transport and logistics system (TLS) of the Republic of Azerbaijan as a strategic component of sustainable economic growth and diversification. The research highlights the country‟s efforts to develop its non-oil sectors and transform its advantageous geographic position into a key transit hub between Europe and Asia through large-scale infrastructure projects, including the Baku–Tbilisi–Kars, North–South, Trans-Caspian, and Zangezur corridors. The study aims to assess the institutional, infrastructural, economic, and environmental factors influencing the performance and competitiveness of Azerbaijan‟s TLS. The methodological framework is based on the works of domestic and international scholars, as well as statistical, comparative, and factor analysis using national transport data for 2020–2024. The study identifies the main global trends shaping the logistics sector, such as digitalization, automation, environmentally friendly technologies, and multimodal integration. Quantitative analysis of freight transportation volumes, costs, and revenues by transport mode reveals a steady increase in road and pipeline transport, improving operational efficiency despite cost fluctuations. The SWOT analysis confirms that Azerbaijan‟s strengths lie in its strategic location, modernizing infrastructure, and state support, while weaknesses include limited qualified personnel and the need for further environmental adaptation. The results show that the TLS plays an essential role in enhancing Azerbaijan‟s economic competitiveness by facilitating trade, attracting investment, and reducing transaction costs. Strategic priorities include strengthening institutional coordination, digital transformation, human capital development, and the transition to green logistics. The study concludes that sustainable progress in Azerbaijan‟s transport and logistics system will depend on the effective integration of infrastructure modernization, innovation, and environmental policy. Future research should focus on developing quantitative models to measure the TLS‟s contribution to GDP growth and long-term economic sustainability.
Економічна оцінка внеску транспортно-логістичної системи у національне економічне зростання
Keywords: transport and logistics system; logistics; socio-economic development; transport; logistics services; транспортно-логістична система; логістика; соціально-економіч- ний розвиток; транспорт; логістичні послуги; 338.47;333.3; 10.30977/ЕТК.2225-2304.2025.46.233